The Frequency of Elderly Patients with Diabetes Type II Having Risk of fall and Impaired Balance; A Cross Sectional Survey - Ayesha Alam, Usman Zahoor Anjum, Kinza Idrees, Hamna Rahman, Malia, Rabia Arif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes Mellitus type 2 causes multiple complications like peripheral neuropathy, retinopathy and vestibulopathy. Diabetic neuropathy was one of the very common and long-term complications of DM which worsen throughout time. Postural variability and balance illness were mutual findings in DN due to lessened proprioception. Objective: The objective was to determine the frequency of elderly patients with diabetes type II having risk of Fall and impaired Balance. Methods: It was a cross sectional study. The Sample size was 133 participants surveyed through convenient sampling technique. Total time from May to October 2021 was utilized for study. Berg Balance Scale was used to determine the risk of fall in older adults having diabetes mellitus type 2. Participants were appearing for assessment for once. Data was analyzed on SPS S version 25. Results: The result showed that 76.7% patients were independent in their daily life activities. The results of our study were that total 23.3% patients were at the risk of fall. The means and standard deviation of total score of Berg Balance Scale was found to be 44.49±10.48. Conclusion: Based on findings of study it was concluded about one fourth of patients were at risk of fall and impaired balance. The adverse effects associated with diabetes mellitus like retinopathy, vestibulopathy and diabetic neuropathy may contribute to worsening balance and fall risk. Keywords: Vestibulopathy, Berg Balance Scale, Diabetic Neuropathy, Balance Impairment, Retinopathy